Analysis of Foot Type in Korean Young Adults Based on Normalized Arch Height - Do-young Jung (Korean Research Society of Physical Therapy, 2020)
Background: The classification of foot type can be commonly determined by the height of the media longitudinal arch. The normalized arch height (NAH) is defined as the ratio of navicular or instep heights to the foot length or instep length. Objects: This study investigated the relationships among foot characteristics, such as foot length (FL), instep length (IL), navicular height (NH), and instep height (IH), in Korean young adults. Also, the distribution of foot type based on calculated NAH was assessed. Methods: Three-dimensional foot scanning data of young adults aged 20 to 39 years (total: 1,978; 974 male, 1,004 female) were obtained from the Korea Technology Standards Institute, and used for analyses. NAH was calculated as the following: NH/FL, IH/FL, IH/IL, NH/ IL. Spearman's rank order correlation was used to identify correlations among variables. The Mann-Whitney U-test and chi-square test were used to compare the sex differences in foot characteristics and distribution of foot type. Results: FL and IL showed a very high correlation (r = 0.94). The correlations between FL or IL and IH (r = 0.50-0.57) were greater than those between FL or IL and NH (r = 0.23-0.72). Males had significantly larger values than females (p < 0.001), and the frequency of pes planus was significantly higher in females than in males (χ2 = 50.09, p < 0.001). Based on the IH/IL index, the neutral foot, pes planus and pes cavus distributed by 16%, 78%, and 6% respectively. Conclusion: Our results on foot arch distribution could be used as basic data in clinical or footwear fields, and our data on differences in arch structure according to sex may facilitate understanding of why injury to the lower limbs differs between males and females.